Human relationships, psychotherapy and life from an existential perspective - Arbocco de los Heros, Manuel (2019)
This is a text that compiles fifteen paragraphs or titles where a series of reflections is presented about the life and interpersonal relationship, the human being, as well as the psychotherapy. In a critical analysis perspective, but humanistic and hopeful at the same time. It joins other papers presented already in conferences, journals, and newspapers. Also, these topics are always presented in classes at the university and in the dialogues with patients in consultation. We hope they are likely to be of interest and lead to more proposals and studies.